2006
DOI: 10.1111/j.1524-4725.2005.31601
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recurrent Pilonidal Sinus with Laser Epilation

Abstract: Laser epilation of the natal cleft should be considered a first choice treatment for recurrent pilonidal disease. Preventive laser epilation of the natal cleft in patients with recurrent folliculitis could avoid future surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 13 publications
(11 reference statements)
1
31
0
1
Order By: Relevance
“…Long-lasting or permanent hair removal in the gluteal area in pilonidal sinus disease would eliminate the hairs and decrease the risk of recurrent disease. 11,13 The recent literature consists of reports on the benefits of laser epilation in pilonidal sinus disease. Benedetto et al reported two patients with recalcitrant pilonidal sinus disease treated with an 800 nm diode laser, resulting in long term relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-lasting or permanent hair removal in the gluteal area in pilonidal sinus disease would eliminate the hairs and decrease the risk of recurrent disease. 11,13 The recent literature consists of reports on the benefits of laser epilation in pilonidal sinus disease. Benedetto et al reported two patients with recalcitrant pilonidal sinus disease treated with an 800 nm diode laser, resulting in long term relief.…”
Section: Discussionmentioning
confidence: 99%
“…6 In recent years, reports of laser epilation in the pilonidal sinus disease have shown beneficial effect by decreasing the risk of recurrent Pilonidal sinus disease. [7][8][9][10][11][12][13] Excessive hair growth in the natal cleft is thought to be a key factor in initiating these abscess and their recurrence. Hair are often found trapped in the base of pilonidal wounds.…”
Section: Introductionmentioning
confidence: 99%
“…conclude that LHR of the natal cleft should be considered a first‐choice treatment for recurrent PNS. Preventive LHR of the natal cleft in patients with recurrent folliculitis could avoid future surgery 28 . Benedetto and Lewis have treated two patients with recalcitrant PNS by LHR using diode laser 29 …”
Section: Discussionmentioning
confidence: 56%
“…[10–1416–18] In our study, the overall recurrence rate was very low compared to the literature, this is mostly attributed to the long-term laser hair removal in more than half of the cases with no recurrence in such group.…”
Section: Discussionmentioning
confidence: 64%